The Urgent Need for Recommending Physical Activity for the Management of Diabetes During and Beyond COVID-19 Outbreak - Marçal, Isabela Roque; Fernandes, Bianca; Viana, Ariane Aparecida; Ciolac, Emmanuel Gomes (Frontiers in Endocrinology, 2020)
Diabetes is the second most prevalent non-communicable chronic diseases (NCDs) in patients with coronavirus disease 2019 (COVID-19) and is highly associated with increased incidence of disease severity and mortality. Individuals with diabetes and poor glycemic control have an even worse prognosis. Despite of the need/effectiveness of social distancing measures (i.e.: home confinement, quarantine and/or lockdown) during COVID-19 outbreak, preliminary findings showed an increase in negative behaviors during COVID-19 home confinement (i.e.: 33.5% reduction in physical activity, 28.6% ( 3.10h) increase in sedentary behavior (i.e.: daily sitting, reclining and lying down time), and more unhealthy food consumption and meal pattern), which may have important clinical implications. For example, we estimated that this reduction in physical activity can increase the cases of type 2 diabetes (from 7.2% to 9.6%; 11.1 million cases per year) and all-cause mortality (from 9.4% to 12.5%; 1.7 million deaths per year) worldwide. Few weeks of reduction in physical activity levels result in deleterious effects on several cardiometabolic (i.e.: glycemic control, body composition, inflammatory cytokines, blood pressure, vascular function…) and functional parameters (i.e.: cardiorespiratory/muscle fitness, balance, agility…). In contrast, physical activity and exercise are important tools for preventing and treating diabetes and others NCDs. Home-based exercise programs are useful, safe and effective for the management of diabetes, and could be widely used during COVID-19 outbreak. In this context, there is an urgent need for recommending physical activity/exercise, during and beyond COVID-19 outbreak, for improving the management of diabetes, as well as to prevent the increase in global burden of COVID-19, diabetes and others NCDs.